2013
DOI: 10.1080/17523281.2012.725425
|View full text |Cite
|
Sign up to set email alerts
|

Mental health correlates of anger and violence among individuals entering substance use treatment

Abstract: Individuals with substance use disorders (SUDs) have consistently been shown to report elevated levels of anger and rates of violence perpetration. Given that heightened anger can increase risk for violence and also impede treatment for SUD, it is important to identify correlates of anger and violence among individuals in SUD treatment settings. While previous research has identified factors associated with anger and violence among individuals with SUD, these studies tend not to adequately address the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
(101 reference statements)
2
3
0
Order By: Relevance
“…Trait physical aggression significantly increased the odds of reporting physical MBA perpetration. This is consistent with results observed in previous research [3, 4, 55], and is expected given trait aggressiveness and engagement in illicit substance use share similar predictors [56]. Furthermore, it has been suggested that an aggressive personality may influence a user's ‘drug of choice’, with such selections facilitating key features of temperament and levels of social deviance [57].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Trait physical aggression significantly increased the odds of reporting physical MBA perpetration. This is consistent with results observed in previous research [3, 4, 55], and is expected given trait aggressiveness and engagement in illicit substance use share similar predictors [56]. Furthermore, it has been suggested that an aggressive personality may influence a user's ‘drug of choice’, with such selections facilitating key features of temperament and levels of social deviance [57].…”
Section: Discussionsupporting
confidence: 90%
“…ATS can also increase wakefulness which can lessen the sedating effects of alcohol and heighten alcohol-related intoxication, which may help explain their significant influence on physical MBA perpetration even after the inclusion of HID in the present study 4.2 | Trait variables, illicit drugs and male barroom aggression Trait physical aggression significantly increased the odds of reporting physical MBA perpetration. This is consistent with results observed in previous research [3,4,55], and is expected given trait aggressiveness and engagement in illicit substance use share similar predictors [56]. Furthermore, it has been suggested that an aggressive personality may influence a user's 'drug of choice', with such selections facilitating key features of temperament and levels of social deviance [57].…”
Section: Amphetamine-type Stimulants and Mbasupporting
confidence: 90%
“…There were differences the strength of the association depending on the measure of violence used. Unadjusted odds ratios were large and consistent for violent behaviour (OR 3.7, 95% CI 3.1–4.5, p < 0.001; i 2 = 34%, p = 0.163) [47], [48], [49], [50], [51]; in contrast there was no significant effect for violent offending (OR 1.0, 95% CI 0.4–2.7, p = 0.961; i 2 = 94%, p < 0.001) [45,[52], [53], [54], [55]]. One large cross-sectional survey of tertiary students found more perpetration of sexual exploitation/abuse among people using amphetamines [50]; another study of substance users found increased likelihood of intimate partner violence among those using amphetamines [56].…”
Section: Resultsmentioning
confidence: 97%
“…Anger was associated with increased substance use and problematic use, demonstrating some of the largest mediated effects [ 27 , 39 , 40 ]. Importantly, anger is associated with poorer substance use treatment outcomes [ 90 ], as well as comorbid mental health problems in those with substance use disorders [ 91 ]. Taken together, these findings suggest anger is an important individual factor to target among young people exposed to adversity to prevent substance misuse.…”
Section: Discussionmentioning
confidence: 99%